Identification of Genes Encoding Antimicrobial Proteins in Langerhans Cells - Oulee, Aislyn; Ma, Feiyang; Teles, Rosane M. B.; de Andrade Silva, Bruno J.; Pellegrini, Matteo; Klechevsky, Eynav; Harman, Andrew N.; Rhodes, Jake W.; Modlin, Robert L. (Frontiers in Immunology, 2021)
Langerhans cells (LCs) reside in the epidermis where they are poised to mount an antimicrobial response against microbial pathogens invading from the outside environment. To elucidate potential pathways by which LCs contribute to host defense, we mined published LC transcriptomes deposited in GEO and the scientific literature for genes that participate in antimicrobial responses. Overall, we identified 31 genes in LCs that encode proteins that contribute to antimicrobial activity, ten of which were cross-validated in at least two separate experiments. Seven of these ten antimicrobial genes encode chemokines, CCL1, CCL17, CCL19, CCL2, CCL22, CXCL14 and CXCL2, which mediate both antimicrobial and inflammatory responses. Of these, CCL22 was detected in seven of nine transcriptomes and by PCR in cultured LCs. Overall, the antimicrobial genes identified in LCs encode proteins with broad antibacterial activity, including against Staphylococcus aureus, which is the leading cause of skin infections. Thus, this study illustrates that LCs, consistent with their anatomical location, are programmed to mount an antimicrobial response against invading pathogens in skin.